Self Image in Media and its Influence on Self esteem: The relevance of Appearance in Total self Evaluation - Llovet, Carmen; Díaz-Bustamante Ventisca, Mónica (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2014)
The analysis about communication of Fashion and Beauty shows the creation of a uniform, manipulated and exclusively physical vision of self. The goal of this paper is to assess the negative influence of this kind of self image on self esteem. Firstly, literature review is done about two concepts: “self concept” and “self esteem”. Secondly, it has been done a desk study related to main economic indicators linked to Fashion and Beauty’s industries. Thirdly, research methodology was applied using descriptive exploratory qualitative and quantitative methods (content analysis, focus group, personal interviews, surveys) among different target (8-37 years old average) affected by the communications of these industries. It is showed a low self esteem related to physical appearance. A growing exposure to images based on unreal bodies makes frustrated and unhappy people. Although people in general are aware of this problem, they find difficult to fight against it.